Validation of the Korean Version of the Delirium Motor Subtype Scale - Kim, Hyunkyung (Psychiatry Investig, 2018)
OBJECTIVE: The Delirium Motor Subtype Scale (DMSS) is a validated and reliable instrument developed from various methods previously used to assess delirium motor subtypes. It focuses on pure motor disturbances with a relative specificity for delirium. The aim of this study was to investigate the validity and reliability of a Korean version of the DMSS (K-DMSS). METHODS: We recruited 145 patients who were older than 60 years and had been referred for psychiatric consultation for delirium. These patients were evaluated using the K-DMSS, Liptzin & Levkoff criteria, and the Korean version of the Delirium Rating Scale-Revised-98 (K-DRS-R98) to compare delirium motor subtypes. RESULTS: The internal consistency of the K-DMSS in assessing delirium motor subtypes was acceptable (Cronbach's alpha=0.79). Delirium motor subtypes identified with the K-DMSS and K-DRS-R98 showed almost perfect agreement (Cohen's Kappa=0.81), while those identified with the K-DMSS and Liptzin & Levkoff criteria showed substantial agreement (Cohen's Kappa=0.78). CONCLUSION: Our results suggest that the K-DMSS is a valid and reliable tool for identifying delirium subtypes.